Blood pressure and risk of breast cancer, overall and by subtypes: a prospective cohort study. Issue 7 (July 2017) - Yang, Yi; Lynch, Brigid M.; Hodge, Allison M.; Liew, Danny; Mclean, Catriona A.; Seviiri, Mathias; Southey, Melissa C.; Hopper, John L.; English, Dallas R.; Giles, Graham G.; Milne, Roger L.; Dugué, Pierre-Antoine
Abstract : Objective: Blood pressure (BP) and breast cancer may share a common pathophysiologic pathway involving chronic inflammation, hormone synthesis and metabolism. Previous studies investigating the association between BP and breast cancer measured BP at a single time point and did not examine associations by breast cancer molecular subtypes. Methods: We used data from 22 833 female participants in the Melbourne Collaborative Cohort Study. BP was objectively measured at baseline (1990–1994) and a follow-up visit (2003–2007). Cox regression was used to estimate hazard ratios for baseline BP and temporal changes in BP in relation to risk of breast cancer, overall and by molecular subtypes. Results: We did not observe any associations between BP measured at baseline and breast cancer risk overall (per 5 mmHg SBP, hazard ratio = 1.00, 95% confidence interval: 0.99–1.02), nor by subtype (per 5 mmHg SBP: estrogen-receptor-negative: hazard ratio = 0.99, 0.96–1.03, progesterone-receptor-negative: hazard ratio = 1.01, 0.99–1.04, human epidermal growth factor receptor 2 negative: hazard ratio = 1.00, 0.98–1.01). Temporal changes in BP were not associated with risk of breast cancer (per 5 mmHg change in SBP, hazard ratio = 1.00, 0.97–1.03). Increased DBP over time was associated with higher risk of triple-negative breast cancer ( P  = 0.04), based on a small number of cases ( N  = 41). Conclusion: Our study supports previous findings of no association between BP and breast cancer. Similar conclusions were reached when assessing BP over time and when examining specific tumor subtypes.